Scheduling Optimization of Swakelola Projects in The Irrigation Water Utilization Improvement Program (P3-TGAI) - Musa Mardwiana Thohir; Anak Agung Bagus Dinariyana Dwi Putranta; Adithya Sudiarno (IPTEK Journal of Proceedings Series, 2020)
The Irrigation Water Utilization Improvement Program (P3-TGAI) is a program implemented by the Balai Besar Wilayah Sungai Brantas (BBWS) which aims to improve irrigation networks by building tertiary/small canals. Kediri, Trenggalek, Tulungagung, Blitar are one of the regional packages that received the program. In the implementation of P3-TGAI in the area, there were problems with the completion of the program. Monitoring and controlling program are needed to ensure the implementation timeliness. Critical Path Method (CPM) analysis is a method used to estimate the minimum duration of a project by connecting each activity and determine the duration of each activity. This method is carried out through the stages of collecting secondary and primary data to identify internal and external factors that affect the speed of the program. Project management analysis method is used to approach the monitoring and controlling program so that it is timely. The expected result from CPM analysis is to get an optimal program design schedule for the implementation of P3-TGAI.